Molecular mechanisms underlying the neuroprotective effect of IGF-1 in neuroblastoma cells and the pro-metastatic effect of Dph3 in murine melanoma cells - Wang, Lei (2013)
Parkinson’s disease (PD) is mainly caused by the lost of dopaminergic neurons located in the substantia nigra pars compacta (SNpc). Thus, preventing the death of dopaminergic neurons is thought to be a potential strategy to interfere with the development of PD. The involvement of IGF-1 signaling pathways in neuronal cell survival has been identified in many cell types, but its downstream targets are frequently cell type-specific. In the present work, we studied the effect of IGF-1 on MPP+-induced apoptosis in human dopaminergic neuroblastoma SH-EP1 cells. We found that IGF-1 effectively protects SH-EP1 cells against MPP+-induced apoptotic cell death. We further delineated the underlying molecular mechanism and showed the PI3K/AKT pathway plays a central role in IGF-mediated cell survival against MPP+ neurotoxicity, not the mitogen-activated protein kinase (MAPK)/ERK pathway. Moreover, we demonstrated that the protective effect of AKT is largely dependent on the inactivation of glycogen synthase kinase 3β (GSK-3β), since inhibition of GSK-3β by its inhibitor, BIO, could mimic the protective effect of IGF-1 on MPP+-induced cell death in SH-EP1 cells. Interestingly, the IGF-1 potentiated PI3K/AKT activity is found to negatively regulate the c-Jun N-terminal protein kinase (JNK) related apoptotic pathway and this negative regulation is further shown to be mediated by AKT-dependent GSK-3β inactivation. Thus, our findings may provide a better understanding of the neuroprotective mechanism of IGF-1 on dopaminergic neuronal cell death and could hold tremendous implication for the development of therapy to arrest the progression of PD in the future.